The relationship between communication practices and perception about performance within the team - Dong, Yao (2015)
Teamwork is widely acknowledged as the way to face today’s environment and to create a flexible high performance organization to deal with the ongoing change. This study is focus on the communication practices that affects team performance in organization. The three research objectives of this study are to assess the relationship between leader communication practices and performance perception within the team, to examine the relationship between members’ communication practices and performance perception and to investigate the influence of team leader communication and members’ communication on team performance perception. This study has been conducted at XinHua Bookstore in Gansu, China, 175 respondents were employed for final analysis. The results reveal that team leader communication practices and members’ communication practices significantly relate to team performance. All independent variables are related to team performance. Meanwhile, the members’ communication practice is a more powerful influential factor towards team performance. In short, the communication practice has numerous imperative implications for foremost and running team performance in an organization. A highly empowered, motivated, trusted and supported team interaction of members should be highly valued by all the organizations.